Students’ Literacy Abilities in Reading Comprehension through Cooperative Integrated Reading Composition (CIRC) Model - Maryani, N; Sujana, Atep; Sopandi, Wahyu; Rahman, Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
In general, students’ literacy in Sumedang district was categorized as low. Therefore, this qualitative study, conducted to 25 students at Panyingkiran Elementary School 3 Sumedang grade 4th, was carried out to investigate students’ literacy in reading comprehension by applying Cooperative Integrated Reading and Composition (CIRC). The data was collected through observation and questionnaire then strengthening with interview data. Data obtained from these instruments was analyzed qualitatively. The findings indicate that: (1) the use of Cooperative Integrated Reading and Composition (CIRC) learning model could enhance students’ literacy; (2) the use of Cooperative Integrated Reading and Composition (CIRC) could develop students’ initial literacy, in poor, mediocre, or high level; (3) the use of Cooperative Integrated Reading and Composition (CIRC) could develop students’ initial literacy, from poor to mediocre; and (4) the level of literary comprehension was at inferential level